The Anatomy of Criminal Procedure: A Visual Guide to the Law - Coughlan, Stephen Gerard (Irwin Law, 2019)
"The goal of this book is to help render the statutory and common law rules of criminal procedure more comprehensible and accessible to practitioners and students. It presents the law of criminal procedure visually, through a series of annotated charts and diagrams."– Provided by publisher.